A comparative study of the decalcifying capacity of selected citrus fruits on the enamel - Guerrero, Arturo; Magtanong, Danilo L.
This study was done to determine which of the four selected juices of citrus fruits has the greatest decalcifying effect ob the enamel. Two sets on non-carious teeth were used. Four immersion media were prepared namely: calamansi, dayap, dalanghita, and suha. To quantify the amount of declassification of enamel, the immersion media were subjected to the Atomic Absorption Spectroscopy analysis for calcium determination. The results showed that dayap has the greatest decalcifying effect on the enamel, followed closely by calamansi, with dalanghita and suha as the least decalcifying.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Teeth -- Erosion; Fruit juices